Promoting Longevity and Vitality: The Role of Rasayan in Ayurvedic Medicine - Mahajan, Madhavi Prabhakar; Kakde, Payal Chatrabhuj; Pawar, Dhananjay Sakharam; Londhe, Vikrant Arjun; Singh, Shivangi; Shinde, Shreya Rajaram (Journal of Neonatal Surgery, 2025)
Ayurveda is the world's oldest and most authentic medicinal system. The primary goal of Ayurveda is to maintain health and treat sickness. The primary objective of human existence is to live a long and disease-free life by slowing down the ageing process and increasing immunity through a healthy lifestyle. Rasayan, a crucial branch of Ayurveda, focuses on rejuvenation, longevity, and overall well-being. It encompasses herbal formulations, lifestyle practices, and dietary guidelines that enhance physical and mental health by promoting cellular regeneration and immune strength. Rasayan therapy is traditionally used to delay aging, boost immunity, and improve cognitive functions. Key Rasayan herbs such as Ashwagandha, Brahmi, and Amalaki have shown scientific potential in neuroprotection, stress management, and anti-inflammatory effects. A long and healthy life is the key to accomplish the Purushartha Chatustaya in human life as explained in Ayurveda. Acharya Charak gave the first priority to long life among all as described in the first chapter Deerghanjeevitiya Adhyaya. Among all the three snas viz. Praneshna, Dhaneshna & Parlokeshna, the Pranesna is the prime factor to accomplish anything because prana is the base for the others. This article explores the historical foundations, modern scientific validations, and potential applications of Rasayan therapy in holistic health and disease prevention